2019
DOI: 10.1002/bmb.21242
|View full text |Cite
|
Sign up to set email alerts
|

Describing teacher conceptions of technology in authentic science inquiry using technological pedagogical content knowledge as a lens

Abstract: Technology has become an indispensable component of both modern life science and life science education. However, due to inadequate knowledge and experience, teachers are often unable to include technology essential for practicing science in their teaching. In this regard, professional development workshops for in‐service and preservice teachers are beneficial. In this study, we described the role of a professional development workshop in enhancing teachers' technological, pedagogical, and content knowledge th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Science learning, although using ICT media certainly cannot be separated from the scientific stage, this is done to improve students' cognitive skills and motivation to learn. Mishra et al (2019) said that practical work in science education is a unique resource to the learning of scientific knowledge and processes, to the development of important tools and cognitive skills and to enhance students' motivation. Ferreira (2018) reinforces that the social context of the school on science teachers' practices, in terms of the structural and interactional characteristics of the practices and of the level of complexity of knowledge and skills they promote, specifically in the case of practical work contexts.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Science learning, although using ICT media certainly cannot be separated from the scientific stage, this is done to improve students' cognitive skills and motivation to learn. Mishra et al (2019) said that practical work in science education is a unique resource to the learning of scientific knowledge and processes, to the development of important tools and cognitive skills and to enhance students' motivation. Ferreira (2018) reinforces that the social context of the school on science teachers' practices, in terms of the structural and interactional characteristics of the practices and of the level of complexity of knowledge and skills they promote, specifically in the case of practical work contexts.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Common barriers to technology have been investigated, including lack of knowledge, skills, confidence, access, and time (Dinçer, 2018;Kopcha, 2012;Lawrence & Tar, 2018). Also, the conceptual belief of the teachers who perceive that technology is too sophisticated impedes the acceleration of the integration of the technology (Mishra et al, 2019). In line with our study, An & Reigeluth (2011) suggested that implementing professional development is one of five strategies that should be conducted to overcome the general barriers such as knowledge and skills of integrating computational technology for instructional purposes in K-12 schools.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers need to be trained to use new technologies, and they need to be prepared to effectively integrate them into the curriculum to meet the diverse and changing needs of students 16 . There is a need for new professional development to model effective ways to help teachers become comfortable using technology 17 . As a result of all these changes school districts are facing, it is imperative that leaders are preparing teachers by offering continuous support in the form of professional development or teacher training which will enable them to stay abreast with the new forms of technology.…”
Section: Technology Training and Professional Developmentmentioning
confidence: 99%